EFFORTS TO IMPROVE STUDENTS' YELLOW BOOK READING ABILITY USING THE AMSILLATI METHOD - Atus Soliha, Imro; Idris Mohammed Khalil, Abdelmajid; Ahmad Obaidy, Fareed; Sholeh , Anwar (As-Sulthan Journal of Education, 2024)
The aim of this research is to describe learning the yellow book using the fast book reading method, namely the Amsilaty method. The subject of this research is class 2 of Tsanawiyah Madrasah Diniyah Riyadlus Sholihin, Probolinggo City. This research uses Classroom Action Research and is included in the scope of applied research which combines knowledge, research and action . This research uses two cycles, each consisting of planning, implementation, observation and reflection. The data collection technique uses document study in initial conditions. The results of the research show that the use of the Amsilaty method in learning to read the yellow book provides an increase in the ability to read the yellow book of class 2 students at Tsanawiyah Madrasah Diniyah Riyadlus Sholihin, Probolinggo City. In the initial condition it only reached 51%, then in the first cycle it increased to 90% and in the second cycle it increased to 95%.